Gazzâlî ve öncesi dönemde tasavvufta hizmet - Erkul, Adem (My University, 2010)
Gazzâlî ve Öncesi Dönemde Tasavvufta Hizmet Hizmet insanlığın başlangıcından beri varolan bir hâdisedir. Bütün din, kültür ve mistik hareketlerde önemli bir yere sâhip olan hizmet ve hâdimlik, İslâm kültürü içerisinde de önemli bir yer tutmaktadır. Çünkü İslâm’ın insanlara benimsetmek istediği hayât ölçüsü Allah’ın emirlerini yerine getirmek ve yarattıklarına hizmettir. Tasavvufî düşünce bu hayât prensibini gerçekleştirmek için ferdî metodlar uygulayarak insanları eğitir. Bu terbiye metodları arasında hizmet de vardır. Çalışmamız Gazzâlî ve öncesi dönemdeki sûfîlerin hizmet alanları ve anlayışlarına yöneliktir. Gazzâlî, tasavvuf, hizmet, hâdim.

The concept of service in Sufism in Ghazzali and in the pre-Ghazzali period Service is a reality since the beginning of humanity. Service and hadim which has an important role in all religions, cultures and mystical movements has an important place for Islamic culture too. Because, the lifestyle that Islam wants people to get adopted is to fulfill Allah’s orders and to serve the creation of Allah. To perform these vital principles, Sufis developed various methods according to the natures of the disciples. Our thesis will study the methods of serving and their understanding of serving among Sufis that have lived in Ghazzali and in the earlier period. Key words: Ghazzali, sufism, service, hadim
Keywords: Gazzali; İslam Dini; Tasavvuf